Study of Janus Amphiphilic Graphene Oxide as a High-Performance Shale Inhibitor and Its Inhibition Mechanism - Lv, Kaihe; Huang, Pan; Zhou, Zhishi; Wei, Xin; Luo, Qi; Huang, Ziming; Yan, Hui; Jia, Han (Frontiers in Chemistry, 2020)
Janus amphiphilic graphene oxide (JAGO), modified by dodecylamine on one side of graphene oxide (GO), was investigated for its novel use as a shale inhibitor. JAGO was synthesized by the Pickering emulsion template technology and was characterized by the Fourier-transform infrared spectra, UV-vis spectra, and transmission electron microscopy. Compared to KCl (5%), polyether diamine (2%), and pristine GO (0.2%), JAGO's highest shale recovery rate (75.2% at 80°C) and lowest swelling height of Mt-pellets (2.55 mm, 0.2%) demonstrated its excellent inhibitive property. Furthermore, JAGO acted as a perfect plugging agent and greatly reduced filtration loss. Based on the results of X-ray diffraction, contact angle measurements, and pressure transmission tests, we proposed that the 2D nano-sheet amphiphilic structure of JAGO, which enabled it to be effective both in chemical inhibition and physical plugging, was responsible for its remarkable inhibition performances.